2017
DOI: 10.1074/jbc.m117.808287
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-874–mediated inhibition of the major G1/S phase cyclin, CCNE1, is lost in osteosarcomas

Abstract: The tumor microenvironment is characterized by nutrient-deprived conditions in which the cancer cells have to adapt for survival. Serum starvation resembles the growth factor deprivation characteristic of the poorly vascularized tumor microenvironment and has aided in the discovery of key growth regulatory genes and microRNAs (miRNAs) that have a role in the oncogenic transformation. We report here that miR-874 down-regulates the major G/S phase cyclin, cyclin E1 (CCNE1), during serum starvation. Because the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…The data of RT-qPCR analysis indicated that miR-874 (23,24). miR-874 expression is also downregulated in osteosarcoma tissues and cell lines (25,26). Low miR-874 expression is strongly related to TNM stage, tumour size and lymph node metastasis in patients with osteosarcoma (26).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The data of RT-qPCR analysis indicated that miR-874 (23,24). miR-874 expression is also downregulated in osteosarcoma tissues and cell lines (25,26). Low miR-874 expression is strongly related to TNM stage, tumour size and lymph node metastasis in patients with osteosarcoma (26).…”
Section: Discussionmentioning
confidence: 97%
“…In osteosarcoma, miR-874 upregula-. In osteosarcoma, miR-874 upregulation represses cell proliferation, migration and invasion, promotes cell apoptosis in vitro and inhibits tumour growth in vivo (25,26). In breast cancer, ectopic miR-874 expression restricts cell proliferation, increases apoptosis and induces cell cycle arrest (30).…”
Section: Discussionmentioning
confidence: 99%
“…miR-874 has been implicated in the regulation of cancer initiation and progression. For instance, resumption expression of miR-874 suppressed osteosarcoma cell growth and metastasis, increased apoptosis in vitro and reduced tumour growth in vivo (27,34). Numerous studies have indicated that miR-874 upregulation inhibited cell proliferation, induced apoptosis and reversed chemoresistance in colorectal cancer (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from cells using TRIzol reagent (Invitrogen) and reverse-transcribed into cDNA using Moloney murine leukemia virus reverse transcriptase (Invitrogen). For miRNA analysis, total RNA was poly(A)-tailed using Escherichia coli poly(A) polymerase (New England Biolabs) before reverse transcription as described previously (6). The qRT-PCR reactions were carried out in duplicates in a 10-l volume for the expression analysis.…”
Section: Rna Extraction and Quantitative Real-time Pcrmentioning
confidence: 99%